Host Communication Styles and Language Variations in Context of TikTok Live-Streaming Commerce - Muhamad Husni Mubarok; Metha Madonna; Fikri Reza (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
Live-streaming commerce offers a new experience for people in direct buying and selling activities with host plays an important role as an intermediary between sellers and buyers. This research examined the different communication styles and language variations used by hosts in the context of TikTok live-streaming commerce. It explored how hosts engage with their audiences and the language references they employ. This research used a qualitative approach with content analysis methods. The primary data obtained through digital observations on four TikTok Shop accounts that regularly host live streams while interviews are employed as a secondary data. The results showed that hosts predominantly use a task-oriented communication style with emotive behaviors. This style is reflected in the speed and volume of their speech, frequent greetings, and responsive interactions with consumers. Hosts often use informal language, influenced by their linguistic preferences, such as sociolect, which varies by age. It is beneficial for hosts to develop an idiolect to differentiate themselves from others by creating certain unique words or sentences. Overall, live-streaming commerce has created a unique shopping culture where hosts must quickly and clearly explain product details while maintaining effective communication with buyers for a reciprocal exchange of information.